Co-Transformation of Type and Instance Graphs Supporting Merging of Types and Retyping - Mantz, Florian; Taentzer, Gabriele; Lamo, Yngve (Electronic Communications of the EASST, 2013)
Algebraic graph transformation is a well-known rule-based approach to manipulate graphs that can be applied in several contexts. In this paper we use it in the context of model-driven engineering. Graph transformation rules usually specify changes to only one graph per application, however there are use cases such as model co-evolution where not only a single graph should be manipulated but also related ones. The co-transformation of type graphs together with their instance graphs has shown to be a promising approach to formalize model and meta-model co-evolution. In this paper, we extend our earlier work on co-evolution by allowing transformation rules that have less restrictions so that graph manipulations such as merging of types and retyping of graph elements are allowed.